If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 20 = 2y + -40 Reorder the terms: 20 + Y = 2y + -40 Reorder the terms: 20 + Y = -40 + 2y Solving 20 + Y = -40 + 2y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + Y = -40 + -20 + 2y Combine like terms: 20 + -20 = 0 0 + Y = -40 + -20 + 2y Y = -40 + -20 + 2y Combine like terms: -40 + -20 = -60 Y = -60 + 2y Simplifying Y = -60 + 2y
| 7x+15=4x+27 | | 2x^2+11=-10n | | 7p=7(5p+7) | | 3x-16i=12+(2y)i | | (8y-2)+(6y+6)=158 | | p+40=6p | | 5(n+2)-3(3n-5)=12 | | 5x^2-54=3x | | 9B=B+24 | | 11g+h=-5 | | 4.22-0.14x=5x-2.205 | | -7x+3(x+4)=8 | | 23/9*3 | | -24+2m=-22 | | 7k^2-20=-10k | | 14/18=42/? | | -2(v-2)=-4v-4 | | 12+24=-36t | | 8m-5+2m= | | 7/9=c/18 | | 4n^2+3=-5 | | 2y+6+3y=-7+2 | | (X-4.95)/x | | 17/5*4 | | X^2-3Z=5 | | -6w+4(w-8)=-12 | | 4n^2-13=-9 | | (2+4p)(5)= | | 7y=4y+30 | | (3v)-(12)=15 | | 5y+8x+5=180 | | 4x^2-11=47 |